Low-density and high-compression-resistance rigid polyurethane foam as well as preparation method and application thereof

Through the copolymerization reaction of polyether/polyester polyol and 4110 polyether, low-density, high compression-resistant hard polyurethane foam is prepared, which solves the problems of complex process and poor performance trade-offs in the prior art, and realizes the lightweight and high-strength application of the material.

CN119775524APending Publication Date: 2025-04-08SICHUAN UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411973534.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

The prior art is difficult to meet the needs of industrial production and application when preparing low-density, high compression-resistant hard polyurethane foam.

Method used

Low-density, high compression-resistant hard polyurethane foam is prepared by copolymerization using different types of polyether/polyester polyols and 4110 polyether, and one-step molding technology is used to simplify the production process.

Benefits of technology

It has achieved a combination of low density and high compression resistance. The material has good bending resistance, impact resistance, low water absorption, damping performance and machining operability. It is suitable for aerospace, marine engineering and other fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005219947960000091
    Figure BDA0005219947960000091
  • Figure BDA0005219947960000111
    Figure BDA0005219947960000111
  • Figure BDA0005219947960000121
    Figure BDA0005219947960000121
Patent Text Reader

Abstract

The invention belongs to the technical field of synthesis and preparation of advanced materials, and particularly relates to low-density and high-compression-resistance rigid polyurethane foam as well as a preparation method and application thereof. According to the invention, the polyurethane rigid foam material with low density and excellent compressive property is prepared through copolymerization of various polyether or polyester polyol. The polyurethane rigid foam prepared by the invention also has good bending resistance, impact resistance, water resistance, damping performance and machinable operability, and shows good application prospects in the fields of aerospace, ocean engineering, ship transportation, military equipment, automobile industry and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of advanced material synthesis and preparation, and specifically relates to a low-density, high-compression-resistant rigid polyurethane foam and a preparation method and application thereof. Background Art

[0002] Rigid polyurethane foam (RPUF) is made by reacting polyether (or polyester) polyols and polyisocyanates in the presence of blowing agents, catalysts, foam stabilizers and other additives. RPUF plays an important role in modern industry and technology and is widely studied and applied in the fields of aerospace, marine engineering, shipping, military equipment and automobile industry.

[0003] The density of rigid polyurethane foam is an important factor affecting performance. For compressive strength, the relationship between strength and density basically conforms to log(strength)=logA+B*log(density). From the formula, it can be seen that the compressive strength and density of the material basically show a positive correlation trend, and the properties such as bending strength and compression modulus can also be predicted by this formula. With the rapid development of aerospace, deep-sea ocean and artificial intelligence, higher demands are placed on lightweight and high-strength materials. In the field of marine engineering equipment and components, in order to realize the detection, observation and other scientific operations of marine detectors in seawater, a low-density, high-strength, hydrostatic external pressure-resistant and low-water absorption foam material is essential for modern deep-sea diving technology. In the field of aerospace, when used as a structural material, it requires low density to achieve its lightweight application, improve transportation efficiency and reduce weight, and also needs to have a good bearing capacity for external forces, maintain the stability of the shape and structure of the device, and ensure the safety of spacecraft, satellites and other spacecraft. In wearable devices (such as VR glasses, smart helmets, etc.), the equipment needs to have excellent lightweight effect and high strength to maintain wearing comfort, prevent deformation or damage to the device shell, and extend the service life of the equipment, considering the long-term wearing of the equipment and the impact and collision during use. In the field of shipbuilding, materials with sufficient strength are also needed to cope with the impact and collision of waves. The lower density provides sufficient buoyancy and reduces the weight of the ship, improving transportation efficiency and ensuring ship safety.

[0004] In order to produce rigid polyurethane foam materials with both low density and high strength, domestic and foreign researchers have carried out a lot of research. At present, the density of polyurethane foam is mostly less than 50kg / m 3 , and its compression strength is less than 0.2MPa. For example, Li Qiqi used carbon fiber to modify rigid polyurethane foam (Li Qiqi. Preparation and performance characterization of high foaming and high strength rigid polyurethane foam [D]. Tianjin University of Science and Technology, 2023.) to prepare high-strength rigid polyurethane foam. The density of the polyurethane foam material is 33.9kg / m 3, the compression strength is only 0.20MPa, which makes it difficult to use as a structural material, and its application value in aerospace, marine engineering and other fields is low. Zhu Gaofeng et al. used ethylene glycol terephthalate as raw material and adopted a one-step foaming method to prepare a rigid polyurethane foam with a certain strength (Zhu Gaofeng, Ge Mingqiao, Yu Tianshi. Preparation and characterization of rigid polyurethane foam materials [J]. New Chemical Materials, 2017, 45(09): 207-208+211). When the density of the polyurethane foam is 109kg / m 3 Its compressive strength is 1.36MPa, and its lightweight and high-strength application is also very challenging.

[0005] Therefore, in order to obtain a low-density rigid polyurethane foam with excellent compressive resistance and meet the corresponding design requirements, it is necessary to enhance its compression performance. Generally speaking, reinforcing materials are added to improve the compression performance of rigid polyurethane foam, such as various fibers. Generally, chopped fibers (chopped glass fibers, chopped carbon fibers, etc.) are selected, but factors such as the fiber model, length, diameter and modulus need to be considered. These factors will affect the dispersion of the fibers in the foam and reduce the reinforcement effect. Particle filler reinforcement technology is also commonly used. Particle fillers include traditional particle fillers such as hollow glass microspheres and silica. Nanomaterials such as graphene and nano-titanium dioxide can also be selected to significantly improve the compression performance of the foam. However, the large amount of particle fillers used significantly reduces the dispersibility, which will become a defect of the material. From the perspective of the type of crosslinker, more crosslinking sites can be generated during the foaming process by replacing crosslinkers with high functionality (such as four functionalities), and the molecular chains form a tighter three-dimensional network structure, thereby improving the compressive strength and compression modulus of the material. However, the crosslinking reaction will be more complicated, and the crosslinking conditions need to be strictly controlled, otherwise the foam brittleness will increase. By adjusting the concentration of the foaming agent, the type and amount of the foam stabilizer, the size, shape and distribution of the pores of the polyurethane foam can also be controlled to improve its compression performance. However, this will increase the density to a certain extent, and too dense pores will reduce its thermal insulation capacity. Therefore, when enhancing the compression resistance, the existing technology has the problems of complex preparation process and performance trade-off, which is not conducive to industrial production and application.

[0006] Therefore, finding a simple preparation method to prepare low-density, high-compression-resistance rigid polyurethane foam is a problem and challenge faced by the art. Summary of the invention

[0007] In view of the defects of the prior art, the present invention provides a modified polyurethane material and a preparation method thereof, aiming at preparing a low-density, high-compression-resistant rigid polyurethane foam.

[0008] The present invention provides a low-density, high-compression-resistant rigid polyurethane foam, which is prepared by using raw materials including the following parts by weight:

[0009] Polyether / polyester polyol A 75-150 parts,

[0010] Polyether / polyester polyol B 5-25 parts,

[0011] Chain extender 3-24 parts,

[0012] 5-30 parts of cross-linking agent,

[0013] 0.5-3 parts of foaming agent;

[0014] 150-270 parts of isocyanate;

[0015] The polyether / polyester polyol B is selected from at least one of polypropylene glycol PPG-400 and tetramethylene glycol PTMG-650.

[0016] Preferably, the isocyanate index R is 1 to 1.25.

[0017] Preferably, the polyether polyol A is selected from 4110 polyether polyol, 8345 polyether polyol, 2490 polyether polyol, and the polyester polyol A is selected from polyethylene phthalate diol, polyneopentyl phthalate diol, and PS-3512 phthalic anhydride polyester diol.

[0018] Preferably, the chain extender is selected from at least one of 1,2-propylene glycol, ethylene glycol, 1,2-pentanediol, 1,2-octanediol, diethylene glycol, 4,4-bis-sec-butylaminodiphenylmethane, and toluenediamine.

[0019] Preferably, the cross-linking agent is selected from at least one of propylene glycol, trimethylolethane, diethanolamine, triethanolamine, and diethylenetriamine; and / or the foaming agent is water.

[0020] Preferably, the isocyanate is polyphenyl polymethylene polyisocyanate.

[0021] The present invention provides a low-density, high-compression-resistant rigid polyurethane foam as described in any one of the above items, which is prepared by a method comprising the following steps:

[0022] Step 1, polyether / polyester polyol A is mixed with polyether / polyester polyol B, a chain extender, a crosslinking agent, and a foaming agent to prepare a polyol mixture;

[0023] Step 2, isocyanate reacts with the polyol mixture and ages to obtain a product.

[0024] Preferably, in step 1, the mixing is mixing polyether / polyester polyol A with polyether / polyester polyol B, a chain extender, a cross-linking agent, a foaming agent, a foam stabilizer, an amine catalyst and an antioxidant;

[0025] The weight ratio of polyether / polyester polyol A to foam stabilizer, amine catalyst and antioxidant is 75-150:1-4:0.1-1.0:0.5-4;

[0026] The foam stabilizer is selected from S-6920 foam stabilizer, B8423 foam stabilizer, B8433 foam stabilizer and B8404 foam stabilizer; and / or, the amine catalyst is 2040 catalyst; and / or, the antioxidant is selected from pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], 3-thiodiethylenebis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], triethylene glycol bis-[3-(3-tert-butyl-4-hydroxy-5-methylphenyl)propionate].

[0027] Preferably, in step 1, the mixing is stirring at a speed of 2800 to 7000 r / min for 30 to 80 s;

[0028] And / or, in step 2, the reaction is that isocyanate is added to the polyol mixture, stirred at a speed of 2800 to 7000 r / min for 20 to 25 seconds, and the uniformly mixed material is poured into a mold and foamed for 180 to 400 seconds;

[0029] And / or, in step 2, the aging is curing at 20-25° C. for 20-26 hours.

[0030] The present invention provides a method for preparing the low-density, high-compression-resistant rigid polyurethane foam described in any one of the above, which comprises the following steps:

[0031] Step 1, polyether / polyester polyol A is mixed with polyether / polyester polyol B, a chain extender, a crosslinking agent, and a foaming agent to prepare a polyol mixture;

[0032] Step 2, isocyanate reacts with the polyol mixture and ages to obtain a product.

[0033] The present invention also provides the use of the low-density, high-compression-resistant rigid polyurethane foam described in any one of the above items as a material in the fields of aerospace, marine engineering, ship transportation, military equipment, protective equipment, and automobiles.

[0034] The numbering of terms such as "A" and "B" only serves to distinguish different terms, does not indicate any priority or order, and does not limit the scope of the description of technical features.

[0035] The present invention provides a low-density, high-compression-resistant rigid polyurethane foam. Through the copolymerization reaction of polyethers and polyester polyols of various special structures, the specific molecular structure design of the rigid polyurethane foam is realized, and a series of low-density, high-compression-resistant rigid polyurethane foam materials are prepared. These materials have low density and excellent compression resistance. In addition, the polyurethane material prepared by the present invention also has good bending resistance, impact resistance, low water absorption, damping performance and processability, and shows development potential in the fields of aerospace, marine engineering, ship transportation, military equipment, and automobile industry, and has good application prospects.

[0036] The present invention uses different types of polyether / polyester polyols to copolymerize with 4110 polyether, and does not need to introduce fillers with a density higher than that of rigid polyurethane foam, which will not cause a sudden increase in density and affect lightweight applications. The one-step molding technology of this solution only requires preheating of the solid polyether / polyester polyol, and does not require the addition of dispersants, modifiers, or the use of ultrasonic dispersion equipment. Compared with other solutions, the production process is simpler, the production efficiency is higher, it is suitable for large-scale preparation, and has good industrial application value.

[0037] Compared with the addition of chopped fibers, low-density foam has poor bonding performance with fibers and cannot play a reinforcing role. When filament fibers are added, fiber agglomeration occurs, resulting in stress concentration in the foam. After adding fibers, the density of polyurethane foam increases, which will also affect its lightweight application. From the perspective of adding particle reinforcement materials, new nanofillers such as carbon nanotubes, graphene, nanoclay, etc., due to their large specific surface area, need to be surface modified or use dispersion equipment to solve the problem of poor dispersion. Traditional particle reinforcement fillers, such as calcium carbonate and hollow glass microspheres, although they will not have a significant impact on density, as the amount added increases, the raw materials are difficult to mix, and the amount added during use is large, the improvement effect is limited, and excessive addition will also reduce performance. In terms of crosslinking agents, the use of high-functionality crosslinking agents requires strict control of the type, amount, reaction temperature and time of the crosslinking agent, which complicates the production process, and excessive crosslinking will reduce the toughness and impact resistance of the foam. By optimizing the foaming process, such as adjusting the type and amount of foaming agent, foaming temperature control, the ratio between components, catalyst dosage, etc., the foam pore structure and density can be adjusted and the compression performance can be enhanced, but the foam density will usually increase.

[0038] Obviously, according to the above contents of the present invention, in accordance with common technical knowledge and customary means in the art, without departing from the above basic technical ideas of the present invention, other various forms of modification, replacement or change may be made.

[0039] The above contents of the present invention are further described in detail below through specific implementation methods in the form of embodiments. However, this should not be understood as the scope of the above subject matter of the present invention being limited to the following examples. All technologies realized based on the above contents of the present invention belong to the scope of the present invention. DETAILED DESCRIPTION

[0040] In the following examples and experimental examples, reagents and materials not particularly described are all commercially available.

[0041] In the following examples, different chain extenders were selected, and the amount of the chain extender was converted according to the hydroxyl value parameter.

[0042] Example 1 A modified rigid polyurethane foam material and a preparation method thereof

[0043] First, place 4110 polyether polyol in a refrigerator at 5°C for 24h. Then, add 90.05g 4110 polyether polyol, 10.01g phthalic anhydride polyester polyol PA (CAS No.: 32472-85-8), 7.36g 1,2-propylene glycol, 9.01g propylene glycol, 1.31g water, 2.10g S-6920 foam stabilizer, 0.405g 2040 catalyst and 1.84g tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionic acid] pentaerythritol ester to the container. Stir the agitator at 3000r / min for 75s to allow the polyether polyol mixture to be fully mixed. Weigh 192.47g polyphenyl polymethylene polyisocyanate, the isocyanate index R is 1.05. After the stirring is completed, the isocyanate is quickly added to the polyol mixture and stirred at a speed of 3000r / min for 20-25s. Finally, the stirred combination is poured into the mold for foaming for 294s. After the foaming process is completed, it is aged at room temperature for 24h and then taken out for use.

[0044] Example 2 A modified rigid polyurethane foam material and a preparation method thereof

[0045] The method of Example 1 is followed, except that phthalic anhydride polyester polyol PA is replaced by polypropylene glycol PPG-400, the amount of 4110 polyether polyol is 90.01 g, the amount of 1,2-propylene glycol is 7.35 g, the amount of water is 1.305 g, the amount of S-6920 foam stabilizer is 2.11 g, the amount of 2040 catalyst is 0.40 g, the amount of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate is 1.85 g, and the amount of polyphenyl polymethylene polyisocyanate is 196.45 g.

[0046] Example 3 A modified rigid polyurethane foam material and its preparation method

[0047] The method of Example 1 is followed, except that phthalic anhydride polyester polyol PA is replaced by polypropylene glycol PPG-600, the amount of 4110 polyether polyol is 90.04 g, the amount of 1,2-propylene glycol is 7.35 g, the amount of 2040 catalyst is 0.41 g, the amount of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate is 1.85 g, and the amount of polyphenyl polymethylene polyisocyanate is 189.41 g.

[0048] Example 4 A modified rigid polyurethane foam material and its preparation method

[0049] The method of Example 1 is followed, except that phthalic anhydride polyester polyol PA is replaced by polypropylene glycol PPG-1000, the amount of 4110 polyether polyol is 90.04 g, the amount of propylene glycol is 9.00 g, the amount of water is 1.30 g, the amount of S-6920 foam stabilizer is 2.105 g, the amount of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate is 1.85 g, and the amount of polyphenyl polymethylene polyisocyanate is 188.07 g.

[0050] Example 5 A modified rigid polyurethane foam material and its preparation method

[0051] The method of Example 1 is followed, except that 10.01 g of phthalic anhydride polyester polyol PA is replaced by 10.02 g of tetrahydrofuran polyether PTMG-650, the amount of 4110 polyether polyol is 90.06 g, the amount of 1,2-propylene glycol is 7.34 g, the amount of water is 1.30 g, the amount of S-6920 foam stabilizer is 2.105 g, the amount of 2040 catalyst is 0.40 g, the amount of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate is 1.85 g, and the amount of polyphenyl polymethylene polyisocyanate is 186.84 g.

[0052] Example 6 A modified rigid polyurethane foam material and its preparation method

[0053] According to the method of Example 1, the difference is that phthalic anhydride polyester polyol PA is replaced by tetramethylene ether PTMG-1000, the amount of 4110 polyether polyol is 90.01g, the amount of 1,2-propylene glycol is 7.35g, the amount of water is 1.30g, and the amount of polyphenyl polymethylene polyisocyanate is 187.31g. Tetramethylene ether PTMG-1000, due to the increase in molecular weight, the material is in a waxy solid state and needs to be placed in a 50°C oven for 30 minutes in advance to ensure that the material has sufficient fluidity.

[0054] Example 7 A modified rigid polyurethane foam material and its preparation method

[0055] According to the method of Example 1, the difference is that phthalic anhydride polyester polyol PA is replaced by tetrahydrofuran polyether PTMG-2000, the amount of 4110 polyether polyol is 90.04g, the amount of 1,2-propylene glycol is 7.34g, the amount of glycerol is 9.04g, the amount of S-6920 foam stabilizer is 2.11g, the amount of 2040 catalyst is 0.395g, and the amount of polyphenyl polymethylene polyisocyanate is 188.40g. Tetrahydrofuran polyether PTMG-2000, due to the increase in molecular weight, the material is in a waxy solid state and needs to be placed in a 50°C oven for 30 minutes in advance to ensure that the material has sufficient fluidity.

[0056] Comparative Example 1

[0057] The preparation method of Example 1 is followed, except that phthalic anhydride polyester polyol PA is not used, the amount of 4110 polyether polyol is 100.01 g, the amount of 1,2-propylene glycol is 7.35 g, the amount of glycerol is 9.00 g, the amount of water is 1.15 g, the amount of S-6920 foam stabilizer is 2.11 g, the amount of 2040 catalyst is 0.40 g, and the amount of polyphenyl polymethylene polyisocyanate is 173.73 g.

[0058] Comparative Example 2

[0059] The preparation method of Example 1 is followed, except that phthalic anhydride polyester polyol PA is not used, the amount of 4110 polyether polyol is 100.04 g, the amount of 1,2-propylene glycol is 7.345 g, the amount of water is 1.11 g, the amount of S-6920 foam stabilizer is 2.12 g, the amount of 2040 catalyst is 0.41 g, the amount of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate is 1.85 g, and the amount of polyphenyl polymethylene polyisocyanate is 173.73 g.

[0060] Comparative Example 3

[0061] The preparation method of Example 1 is followed, except that phthalic anhydride polyester polyol PA is not used, the amount of 4110 polyether polyol is 100.02 g, the amount of 1,2-propylene glycol is 7.34 g, the amount of water is 1.09 g, the amount of S-6920 foam stabilizer is 2.105 g, and the amount of polyphenyl polymethylene polyisocyanate is 189.39 g.

[0062] Comparative Example 4

[0063] The method of Example 1 is followed, except that 10.01 g of phthalic anhydride polyester polyol PA is replaced by 10.00 g of polypropylene glycol PPG-200, the amount of 4110 polyether polyol is 90.04 g, the amount of 1,2-propylene glycol is 7.34 g, the amount of water is 1.30 g, the amount of 2040 catalyst is 0.40 g, and the amount of polyphenyl polymethylene polyisocyanate is 197.51 g.

[0064] Comparative Example 5

[0065] The method of Example 1 is followed, except that phthalic anhydride polyester polyol PA is replaced by polypropylene glycol PPG-1500, the amount of 4110 polyether polyol is 90.13 g, the amount of 1,2-propylene glycol is 7.35 g, the amount of glycerol is 9.00 g, the amount of water is 1.305 g, the amount of S-6920 foam stabilizer is 2.10 g, the amount of 2040 catalyst is 0.41 g, and the amount of polyphenyl polymethylene polyisocyanate is 188.24 g.

[0066] Comparative Example 6

[0067] According to the method of Example 1, the difference is that 10.01g of phthalic anhydride polyester polyol PA is replaced by 10.00g of tetrahydrofuran polyether PTMG-850, the amount of 4110 polyether polyol is 90.06g, the amount of 1,2-propylene glycol is 7.34g, the amount of water is 1.305g, the amount of S-6920 foam stabilizer is 2.105g, the amount of 2040 catalyst is 0.41g, and the amount of polyphenyl polymethylene polyisocyanate is 185.82g. The material of tetrahydrofuran polyether PTMG-850 is in a waxy solid state and needs to be placed in a 50°C oven for 30 minutes in advance to ensure that the material has sufficient fluidity.

[0068] Comparative Example 7

[0069] According to the method of Example 1, the difference is that phthalic anhydride polyester polyol PA is replaced by tetramethylene ether PTMG-2000, the amount of 4110 polyether polyol is 90.04g, the amount of 1,2-propylene glycol is 7.35g, the amount of water is 1.30g, the amount of S-6920 foam stabilizer is 2.105g, and the amount of polyphenyl polymethylene polyisocyanate is 187.67g. Tetramethylene ether PTMG-2000, due to the increase in molecular weight, the material is in a waxy solid state and needs to be placed in a 50°C oven for 30 minutes in advance to ensure that the material has sufficient fluidity.

[0070] The technical solution of the present invention is further illustrated by experiments below.

[0071] In the following experimental examples, the tested materials are rigid polyurethane foam materials prepared according to the methods described in Examples 1-7 and Comparative Examples 1-7, respectively.

[0072] Experimental Example 1 Characterization of Density and Compressive Properties of Polyurethane Materials

[0073] 1. Experimental Methods

[0074] 1. Determination of density

[0075] According to GB / T 6343-2009, after removing the surface skin, the foam is cut into standard cubic samples with a size of 30mm×30mm×30mm. Take 8 samples at random, measure the length, width and height of the samples with a vernier caliper to an accuracy of 0.02mm, and then weigh the mass of the foam samples with an analytical balance. The ratio of the sample mass to the sample volume is the apparent core density of the polyurethane foam.

[0076] 2. Determination of compressive strength and modulus

[0077] Test compressive strength and compressive modulus: refer to GB 8813-2020 "Determination of compression properties of rigid foam plastics", the sample size is 30mm×30mm×30mm, and the compression rate is 3mm / min. The yield strength is selected as the compressive strength, and according to the derived displacement-force curve, the tangent at the maximum slope of the curve is selected, and its corresponding value is the compressive modulus.

[0078] 2. Experimental Results

[0079] The results are shown in Table 1: According to the method of the embodiment of the present invention, the density of the modified polyurethane material prepared by copolymerizing other polyether (or polyester) polyols with 4110 polyether is equivalent to that of the comparative example, or has a small change. This shows that the method of the present invention ensures that the polyurethane material has a lower density.

[0080] From the perspective of compressive strength, compared with the comparative example, the compressive strength of the polyurethane material prepared in the embodiment is significantly increased, and the introduced polyether (or polyester) polyols include phthalic anhydride polyester polyol PA, polypropylene glycol PPG-400, polypropylene glycol PPG-600, polypropylene glycol PPG-1000, tetrahydrofuran polyether PTMG-650, tetrahydrofuran polyether PTMG-1000, 1,4-butanediol-adipate. In particular, when the introduced polyether (or polyester) polyol is polypropylene glycol PPG-400, the increase effect is most significant. The results show that the polyurethane material prepared in the embodiment has an improved ability to resist damage when subjected to compression.

[0081] From the perspective of compression modulus, compared with the comparative example, the compression modulus of the polyurethane materials prepared in Examples 2, 4, and 5 is significantly increased, and the introduced polyether (or polyester) polyols include polypropylene glycol PPG-400, polypropylene glycol PPG-1000, and tetramethylene glycol PTMG-650. In particular, when the introduced polyether (or polyester) polyol is tetramethylene glycol PTMG-650, the increase effect is most significant. The results show that the polyurethane materials prepared in Examples 2, 4, and 5 have a further enhanced ability to resist deformation within the elastic range.

[0082] Table 1 Determination results of density, compressive strength and compressive modulus

[0083]

[0084] The above results show that the polyurethane materials prepared in the examples have improved ability to resist damage when subjected to compression, especially when the polyether (or polyester) polyol introduced in Example 2 is polypropylene glycol PPG-400, the improvement effect is the best; the polyurethane materials prepared in Examples 2, 4, and 5 have enhanced ability to resist deformation within the elastic range, especially when the polyether (or polyester) polyol introduced in Example 5 is tetramethylene glycol PTMG-650, the strengthening effect is the best. Therefore, the compressive resistance of the polyurethane material prepared in this example is improved.

[0085] Experimental Example 2 Characterization of other properties of polyurethane materials

[0086] 1. Experimental Methods

[0087] 1. Determination of flexural strength and flexural modulus

[0088] Bending strength, refer to GB8812.1-2007 "Determination of flexural properties of rigid foam plastics Part 1: Basic bending test" for sample preparation, sample size 120mm×25mm×20mm, span 100mm, test speed 10mm / min. Record its load-strain curve, when the sample is less than 5% strain, record the breaking load. Calculation of bending strength and bending modulus refers to GBT8812.2-2007 "Determination of bending strength and apparent bending elastic modulus".

[0089] 2. Determination of impact strength

[0090] According to GB / T 1043.1-2008 "Determination of impact properties of plastic simply supported beams", the unnotched simply supported beam impact test was carried out, the sample size was 120mm×15mm×10mm, the test span was 70mm, the test pendulum was 2J, and the speed was 2.9mm / s. The fracture strength was selected as the impact strength.

[0091] 3. Determination of non-stick time S

[0092] Test non-stick time: According to the definition of various foaming reaction characteristic parameters, test conditions and test methods in HG / T 4574-2014 "Determination method of foaming reaction characteristics of polyurethane raw materials", non-stick time and other parameters are measured. That is, the time from the beginning of material mixing to the time when the gloved finger or glass rod touches the foam surface without sticking.

[0093] 4. Determination of water absorption

[0094] Select a sample of 150mm×150mm×30mm, and obtain the dry weight m1 and foam volume v by measurement. Immerse the sample in water, and remove bubbles on the surface of the sample with a soft brush or by stirring. Weigh again after 24 hours to obtain the wet weight m2. Water absorption rate = (m2-m1) / v.

[0095] 5. Determination of loss factor Tanδ at 25℃

[0096] Use a vernier caliper to measure the size of the sample, take the average value of multiple position measurements, and record it on the dynamic mechanical analyzer (DMA). Mode selection on the dynamic mechanical analyzer: static load control is controlled by the contact force size, the contact force is 0.1N, the proportional factor is 1.3, and the static strain limit is 1%. Dynamic load control is deformation control, the dynamic deformation is 0.03mm, the dynamic force limit is 20N, the alternating load is none, and the load frequency is 1Hz. Liquid nitrogen refrigeration is selected for atmospheric conditions, and the purge gas is turned on. Maintain a heating rate of 5K / min, increase the temperature from 0℃ to 230℃, and keep warm for 300s. The equipment will record the data of its tanδ changing with temperature in real time. Save the parameters, name the file, and run the program. After completing the experiment, export the data and find the tanδ value at 25℃. Take the average of multiple samples.

[0097] 2. Experimental Results

[0098] The results of other properties are shown in Table 2: Compared with the comparative example, the introduction of other polyether (or polyester) polyols in the preparation method of the embodiment of the present invention did not significantly reduce the bending performance, impact strength, non-stick time, water absorption rate and loss factor of the rigid polyurethane foam. Among them, when the other polyether (or polyester) polyol introduced in Example 3 is polypropylene glycol PPG-600, the bending modulus and impact strength increase most significantly, indicating that the bending resistance and impact resistance of the material are improved; when the other polyether (or polyester) polyol introduced in Example 2 is polypropylene glycol PPG-400, the bending strength increases most significantly, indicating that the force the material withstands during the bending process is enhanced; when the other polyether (or polyester) polyol introduced in Example 7 is 1,4-butanediol-adipate PBA-100, the non-stick time increases the most, indicating that the material has improved processing operability, thermal stability and heat resistance; when the other polyether (or polyester) polyol introduced in Example 1 is phthalic anhydride polyester polyol PA, the water absorption rate decreases the most, indicating that the water resistance of the material is improved; when the other polyether (or polyester) polyol introduced in Example 5 is tetramethylene furan polyether PTMG-650, the loss factor increases the most, indicating that the damping performance of the material is improved.

[0099] Table 2 Determination results of other properties

[0100]

[0101]

[0102] The results show that the present invention introduces other polyether (or polyester) polyols in the preparation method, and the bending resistance, impact resistance, processing operability, water absorption and damping performance of the rigid polyurethane foam will not be significantly reduced. In particular, when the other polyether (or polyester) polyols introduced are phthalic anhydride polyester polyol PA, polypropylene glycol PPG-400, polypropylene glycol PPG-600, tetramethylene glycol PTMG-650, 1,4-butanediol-adipate PBA-1000, other properties are also significantly improved.

[0103] It can be seen from the above embodiments and experimental examples that the present invention provides a low-density, high-compression rigid polyurethane foam. The specific molecular structure design of rigid polyurethane foam is realized by copolymerization of polyether and polyester polyol of various special structures, and a series of low-density, high-compression-resistant rigid polyurethane foam materials are obtained. In particular, when the introduced polyether (or polyester) polyol is polypropylene glycol PPG-400, the compressive strength is the highest; when the introduced polyether (or polyester) polyol is tetrahydrofuran polyether PTMG-650, the compressive modulus is the highest. In addition, the rigid polyurethane foam prepared by the present invention also has good bending resistance, impact resistance, low water absorption, damping performance and processability, and shows development potential in the fields of aerospace, marine engineering, ship transportation, military equipment, and automobile industry, and has good application prospects.

Claims

1. A low-density, high-compression-resistant rigid polyurethane foam, characterized in that: The invention is prepared by using the following raw materials in parts by weight: Polyether / polyester polyol A 75-150 parts, Polyether / polyester polyol B 5-25 parts, Chain extender 3-24 parts, 5-30 parts of cross-linking agent, 0.5-3 parts of foaming agent; 150-270 parts of isocyanate; The polyether / polyester polyol B is selected from at least one of polypropylene glycol PPG-400 and tetramethylene glycol PTMG-650.

2. The low-density, high-compression-resistant rigid polyurethane foam according to claim 1, characterized in that: The isocyanate index R is 1 to 1.

25.

3. The low-density, high-compression-resistant rigid polyurethane foam according to claim 1, characterized in that: The polyether polyol A is selected from 4110 polyether polyol, 8345 polyether polyol, and 2490 polyether polyol, and the polyester polyol A is selected from polyethylene phthalate diol, polyneopentyl phthalate diol, and PS-3512 phthalic anhydride polyester diol.

4. The low-density, high-compression-resistant rigid polyurethane foam according to claim 1, characterized in that: The chain extender is selected from at least one of 1,2-propylene glycol, ethylene glycol, 1,2-pentanediol, 1,2-octanediol, diethylene glycol, 4,4-bis-sec-butylaminodiphenylmethane, and toluenediamine.

5. The low-density, high-compression-resistant rigid polyurethane foam according to claim 1, characterized in that: The cross-linking agent is selected from at least one of propylene glycol, trimethylolethane, diethanolamine, triethanolamine, and diethylenetriamine; and / or the foaming agent is water.

6. The low-density, high-compression-resistant rigid polyurethane foam according to claim 1, characterized in that: The isocyanate is polyphenyl polymethylene polyisocyanate.

7. The low-density, high-compression-resistant rigid polyurethane foam according to any one of claims 1 to 6, characterized in that: It is prepared by a method comprising the following steps: Step 1, polyether / polyester polyol A is mixed with polyether / polyester polyol B, a chain extender, a crosslinking agent, and a foaming agent to prepare a polyol mixture; Step 2, isocyanate reacts with the polyol mixture and ages to obtain a product.

8. The low-density, high-compression-resistant rigid polyurethane foam according to claim 7, characterized in that: In step 1, the mixing is mixing polyether / polyester polyol A with polyether / polyester polyol B, a chain extender, a cross-linking agent, a foaming agent, a foam stabilizer, an amine catalyst and an antioxidant; The weight ratio of polyether polyol A to foam stabilizer, amine catalyst and antioxidant is 75-150:1-4:0.1-1.0:0.5-4; The foam stabilizer is selected from S-6920 foam stabilizer, B8423 foam stabilizer, B8433 foam stabilizer, B8404 foam stabilizer; and / or, the amine catalyst is 2040 catalyst; and / or, the antioxidant is selected from pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], 3-thiodiethylenebis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], triethylene glycol bis-[3-(3-tert-butyl-4-hydroxy-5-methylphenyl)propionate].

9. The method for preparing a low-density, high-compression-resistant rigid polyurethane foam according to any one of claims 1 to 8, characterized in that: The steps include: Step 1, polyether / polyester polyol A is mixed with polyether / polyester polyol B, a chain extender, a crosslinking agent, and a foaming agent to prepare a polyol mixture; Step 2, isocyanate reacts with the polyol mixture and ages to obtain a product.

10. Use of the low-density, high-compression-resistant rigid polyurethane foam according to any one of claims 1 to 8 as a material in the fields of aerospace, marine engineering, ship transportation, military equipment, protective equipment, and automobiles.

Citation Information

Patent Citations

  • Preparation method of rigid spraying polyurethane blended materials for refrigeration house

    CN101735425A

  • Filling reinforcement water plugging polyurethane grouting material and preparation method thereof

    CN110511352A

  • Method for producing rigid polyurethane foams

    CN115838466A

  • Method for preparing a rigid polyurethane foam

    EP4177288A1